Low‐Temperature Charging and Aging Mechanisms of Si/C Composite Anodes in Li‐Ion Batteries: An Operando Neutron Scattering Study. Issue 3 (27th December 2019) - Richter, Karsten; Waldmann, Thomas; Paul, Neelima; Jobst, Nicola; Scurtu, Rares‐George; Hofmann, Michael; Gilles, Ralph; Wohlfahrt‐Mehrens, Margret
Abstract: The addition of Si compounds to graphite anodes has become an attractive way of increasing the practical specific energies in Li‐ion cells. Previous studies involving Si/C anodes lacked direct insight into the processes occurring in full cells during low‐temperature operation. In this study, a powerful combination of operando neutron diffraction, electrochemical tests, and post‐mortem analysis is used for the investigation of Li‐ion cells. 18650‐type cylindrical cells in two different aging states are investigated by operando neutron diffraction. The experiments reveal deep insights and important trends in low‐temperature charging mechanisms involving intercalation, alloying, Li metal deposition, and relaxation processes as a function of charging C‐rates and temperatures. Additionally, the main aging mechanism caused by long‐term cycling and interesting synergistic effects of Si and graphite are elucidated. Abstract : Charge, relax, discharge ! Li distribution in 18650‐type Li‐ion batteries with Si/C composite anode is investigated by operando neutron scattering, which allows the time evolution of the LiC6 and LiC12 reflections to be measured and, combined with electrochemical tests and post‐mortem analysis, reveals details on the charging, relaxation, and aging mechanisms.